Analysis of Geometry Misconceptions In The BSE Book As A 2013 Curriculum Book Reference - Dafid Slamet Setiana; Nuryadi Nuryadi; Rusgianto Heri Santoso (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2019)
This study aims to find out empirical data from the analysis of Electronic School Books (BSE) for students of Class IX Middle Semester I. There are 3 (three) triangles elements, namely the vertex, angle and length of the sides of the triangle, each consisting of 3 (three). But to determine the existence of a triangle requires only two elements, namely the angle and length of the sides of the triangle. However, not the two elements that are used to determine the existence of a triangle, but each must be known. To determine it enough to know 3 (three) elements of the two elements, namely: a. The length of the three sides, b. The length of both sides and one of its angles, c. The length of one side and the size of both angles. The results of the study based on literature review found an error that the BSE Student Mathematics book for class IX contained a triangular image error with 5 elements of two elements (3 side lengths and 2 angles) which proved impossible after analysis using painting and trigonometric calculations.